Church Court Records as Evidence for the Christianisation of Lithuanian Society in the Late-15th and Early-16th Century - S.C. Rowell (Acta Historica Universitatis Klaipedensis, 2014)
This article surveys evidence of Lithuanian social and religious life during the long fifteenth century as revealed by consistory court records from the sees of Płock, Gniezno, Lutsk and Cracow. The dynamics of church court evidence coincide with those of other aspects of Catholic life in the Grand Duchy. Building churches, chantry chapels, funding mansionary priests, selecting particular Masses to be celebrated by your chantry priest (Salve sancta Parens, the Five Wounds of Christ, the Seven Joys of Our Lady), going on pilgrimage, taking part in a procession, venerating the Blessed Sacrament, sending supplications to Rome to obtain permission to own a portable altar or choose a confessor all become much more common in the later decades of the fifteenth century. Cases before the consistory courts in Płock, Gniezno, Vilnius and Lutsk involve a wide social group and deal with a broad range of issues (not just matrimonial disputes or the hiring out of benefices between priests). What we do not find is any obsession with paganism, no use of pagan as an insult, no account of ‘pagan’ practices (or even folk customs, which later become tarred with an ideological brush). Lithuanian dioceses are clearly integrated into the Polish metropolitan sees (Gniezno and also to a lesser degree, Lwów).